The effect of service quality on customer satisfaction in public services / Siti Zuana Abdullah - Abdullah, Siti Zuana (Faculty of Business and Management, 2018)
Service quality has become ever more important to the achievement of customer satisfaction with the increasing complexities of the need and expectation of customers. This research study examines the relationship between service quality dimension and how the dimensions give impacts on customer satisfaction in MARA’s services. Service quality dimensions consist of tangibility, reliability, responsiveness, assurance and empathy. The questionnaires were distributed to 126 customers of MARA’s services in Negeri Sembilan. Convenience sampling was used in this research and data were analyzed using SPSS version 20. The result of the study indicates that there is significant positive relationship between service quality and customer satisfaction of MARA’s services. The results also show that responsiveness has the strongest impact on customer satisfaction.